(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
Poverty is a condition of economic inability to meet the average standard of living of the people in an area. This problem occurs in every country, especially developing countries. Some causes of poverty include uneven distribution of income which can lead to income inequality and low quality of human resources. Various efforts made by the Indonesian government to overcome the problem of poverty include maintaining a rice program for poor families (RASKIN), public health insurance (JAMKESMAS), Cash Direct Assistance (BLT), School Operational Assistance (BOS), National Community Empowerment Program (PNPM ) Mandiri in Urban and Rural Areas, People’s Business Credit (KUR) and so on. The inaccuracy of targets in poverty alleviation caused the goal of alleviating poverty rates far from expectations, as evidenced by the high rate of poverty in West Java Province in 2015. Therefore, it is necessary to know the factors that influence poverty from 27 districts / cities in West Java Province. The independent variables in this study were the average length of school, per capita expenditure, economic growth, education and population. The analysis is used spatial regression with Spatial Autoregressive Models or SAR. The test results show that the average length of school, per capita expenditure, education and population significantly influence poverty, while economic growth has no significant effect. The average variable length of school, per capita expenditure, and population numbers have a negative direction of influence, while the education variable has a positive effect.